Inadequate Preoperative Assessment and Its Clinicopathological Correlates in Patients Referred for Completion Thyroidectomy: A Tertiary Referral Center Analysis - Munawar; R Maman Abdurrahman (HM Publisher, 2026)
Background: Completion thyroidectomy (CT) for differentiated thyroid carcinoma (DTC) is a high-risk procedure, frequently performed following an oncologically incomplete primary operation. This study characterizes the preoperative diagnostic assessment deficiencies in a cohort of DTC patients referred to a tertiary center for re-operation and identifies factors associated with residual disease. Methods: We conducted a retrospective, single-center analysis of all patients who underwent CT for DTC at Hasan Sadikin General Hospital, Indonesia, over a 30-month period (January 1st, 2023, to June 30th, 2025). Data on preoperative assessments at the referring hospitals (ultrasonography (US) quality, fine-needle aspiration biopsy (FNAB), hormonal tests), primary surgical indications, and clinicopathological outcomes from both operations were extracted and analyzed using descriptive and bivariate statistics (Fisher's Exact Test). Results: A total of 27 patients met the inclusion criteria. Analysis of their initial workup revealed significant omissions: 14/27 (51.9%) lacked FNAB, and 5/27 (18.5%) lacked hormonal testing. While 24/27 (88.9%) underwent a primary US, only 20.8% of these reports (5/24) were ATA-compliant staging examinations. Only 5/27 patients (18.5%) received a complete trimodal assessment. Upon re-operation, 10/27 (37.0%) had residual carcinoma. This finding was significantly associated with the omission of primary FNAB (57.1% vs. 15.4%, p = 0.027). Conclusion: In this cohort of referred patients, incomplete preoperative assessment was nearly universal and strongly associated with adverse pathological findings. These data highlight the urgent need for standardized, evidence-based preoperative protocols and strengthened referral systems to ensure patients receive the correct primary operation.